2016
DOI: 10.1007/s12070-016-1000-6
|View full text |Cite
|
Sign up to set email alerts
|

The Epitympanum Revisited: Endoscopic Anatomy

Abstract: In contrast to other means of studying the epitymapnum, the endoscope allows unparallel access without disruption of anatomy. The aim of this study is to delineate the anatomy of the epitympanum through transcanal endoscopy. Systematic dissection of anatomic specimens. We performed systematic endoscopic dissection of 20 ears in 10 fresh frozen anatomical specimens. A detailed flow sheet was filled up documenting the status of the lateral attic folds, the tensor fold, the cog and the tensor folds, the supratuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The anterior epitympanic recess (AER) is frequently involved in chronic infections and represents a common location of the more common pars flaccida growth [8,25]. The complexity of the anatomical architecture of epi-tympanum necessitates accurate and deep knowledge of the surgeon about the spatial relationships present at this site, thus avoiding misguided procedure and inadvertent injury of vital structures [8,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior epitympanic recess (AER) is frequently involved in chronic infections and represents a common location of the more common pars flaccida growth [8,25]. The complexity of the anatomical architecture of epi-tympanum necessitates accurate and deep knowledge of the surgeon about the spatial relationships present at this site, thus avoiding misguided procedure and inadvertent injury of vital structures [8,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The trans-canal endoscopic and microscopic ear surgery approaches offer a new era in the management of limited attic cholesteatoma, providing less invasive surgical technique [21][22][23]. Still, less invasive surgeries are questioning identification of some landmarks; the "Cog" and "KS," both serving as a guidance route to the attic in both approaches [24,25]. The aim of this study is to evaluate a statistical relation between the morphological types of the temporal bone anatomical structures, namely the "cog" and "KS" with an evaluation of their incidence in CSOM with or without cholesteatoma.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies provided important insights on the anatomy as seen by endoscopy. [10][11][12] With the advancement of the angled endoscope and high-resolution camera, it has been possible to look around the corner and magnify small details of this complex anatomy. To summarize the results of these previous anatomical studies, we illustrate a table with the reported findings ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The earlier anatomical studies of the anterior epitympanum were mainly based on histological sections. More recent studies provided important insights on the anatomy as seen by endoscopy 10‐12 . With the advancement of the angled endoscope and high‐resolution camera, it has been possible to look around the corner and magnify small details of this complex anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The structures in this space were described like the ponticulus and subiculum with their variations [27]. The attic also was revisited endoscopically with its two main parts the anterior and posterior epitympanic spaces with clarification of the attic diaphragm [28]. The protympanum was also described endoscopically with its two main conformations with description of the protinuculum separating it from the hypotympanum [29].…”
Section: Role Of Ees In Endoscopic Anatomy and Physiology Of Middle Earmentioning
confidence: 99%